CCL3/Macrophage Inflammatory Protein-1α Is Dually Involved in Parasite Persistence and Induction of a TNF- and IFNγ-Enriched Inflammatory Milieu in Trypanosoma cruzi-Induced Chronic Cardiomyopathy - Gibaldi, Daniel; Vilar-Pereira, Glaucia; Pereira, Isabela Resende; Silva, Andrea Alice; Barrios, Leda Castaño; Ramos, Isalira Peroba; Mata dos Santos, Hílton Antônio; Gazzinelli, Ricardo; Lannes-Vieira, Joseli (Frontiers in Immunology, 2020)
CCL3, a member of the CC-chemokine family, has been associated with macrophage recruitment to heart tissue and parasite control in the acute infection of mouse with Trypanosoma cruzi, the causative agent of Chagas disease. We approached the participation of CCL3 in chronic chagasic cardiomyopathy (CCC), the main clinical form of Chagas disease. We induced CCC in C57BL/6 (ccl3+/+) and CCL3-deficient (ccl3-/-) mice by infection with the Colombian strain. In acute and chronically infected ccl3+/+ mice, high levels of CCL3 mRNA and protein were detected in the heart tissue. Survival was not affected by CCL3 deficiency. In comparison with ccl3+/+, chronically infected ccl3-/- mice presented reduced cardiac parasitism and inflammation due to CD8+ cells and macrophages. Leukocytosis was decreased in infected ccl3-/- mice, paralleling the accumulation of CD8+ T cells devoid of activated CCR5+LFA-1+ cells in the spleen. T. cruzi-infected ccl3-/-mice presented reduced frequency of interferon-gamma (IFNγ)+ cells and numbers of parasite-specific IFNγ-producing cells, while T. cruzi antigen-specific cytotoxic activity was increased. Stimulation of CCL3-deficient macrophages with IFNγ improved parasite control, in a milieu with reduced nitric oxide (NOx) and tumor necrosis factor (TNF), but similar interleukin-10 (IL-10), concentrations. In comparison with T. cruzi-infected ccl3+/+ counterparts, ccl3-/- mice did not show enlarged heart, loss of left ventricular ejection fraction, QTc prolongation and elevated CK-MB activity. Compared with ccl3+/+, infected ccl3-/-mice showed reduced concentrations of TNF, while IL-10 levels were not affected, in the heart milieu. In spleen of ccl3+/+ NI controls, most of the CD8+ T-cells expressing the CCL3 receptors CCR1 or CCR5 were IL-10+, while in infected mice these cells were mainly TNF+. Lastly, selective blockage of CCR1/CCR5(Met-RANTES therapy) in chronically infected ccl3+/+ mice reversed pivotal electrical abnormalities (bradycardia, prolonged PR and QTc interval), in correlation with reduced TNF and, mainly, CCL3 levels in the heart tissue. Therefore, in the chronic T. cruzi infection CCL3 takes part in parasite persistence and contributes to form a CD8+ T-cell and macrophage-enriched cardiac inflammation. Further, increased levels of CCL3 create a scenario with abundant IFNγ and TNF, associated with cardiomyocyte injury, heart dysfunction and QTc prolongation, biomarkers of severity of Chagas’ heart disease.